Relationship of Knowledge with Implementation Personal Hygiene at Food Traders in Pasir Gombong Bekasi Regency - Nur Fauzia Asmi (Lambung Mangkurat, 2022)
Food handlers such as food traders have an important role in food processing because they can transmit disease through food. Food vendors provide personal hygiene such as using mouth coverings, aprons, desserts and coverings in preparing food can trigger events such as diarrhea, poisoning, etc. The purpose of this study was to determine the relationship with the implementation of personal hygiene, such as mouth coverings, use of aprons, food tongs and head coverings in food procesing. The type of research used is observational analytic with a cross sectional study approach. The population in this study were food traders in the Pasir Gombong area with a total sample of 64 people selected based on the lemeshow formula using simple random sampling technique. Data analysis used is chi-square. The results of this study indicate that there is a significant relationship between knowledge and personal hygiene using mouth coverings (p-value 0.005) and aprons (p-value 0.032) and no significant relationship between knowledge and the use of food tongs and head coverings with their p-value 0.111.